SOX2 inhibits LLGL2 polarity protein in esophageal squamous cell carcinoma via miRNA-142-3p. Issue 1 (31st December 2022) - Zhang, Shihui; Chen, Yunyun; Hu, Qiong; Zhao, Tingting; Wang, Zhuo; Zhou, Yijian; Wei, Yuxuan; Zhao, Hongzhou; Wang, Junkai; Yang, Yaxin; Zhang, Jiaying; Shi, Songlin; et al.
ABSTRACT: Elevated SOX2 protein levels correspond to the poor prognosis of patients with esophageal squamous cell carcinoma (ESCC). Poor prognosis is closely correlated with the loss or disruption of cellular polarity; however, the relationships between SOX2 protein and polarity proteins in ESCC remain elusive. Herein, we found that the knockdown of SOX2 significantly decreased miR-142-3p expression and can regulate the translation of LLGL2 protein, a member of the Scribble complex. LLGL2 protein levels in ESCC are negatively correlated with miR-142-3p and SOX2 levels. Moreover, LLGL2 protein expression increased upon SOX2 knockdown in ESCC cell lines, and mutating the binding site for this miRNA in the LLGL2 3'-UTR disrupted its ability to inhibit LLGL2 expression. When LLGL2 was overexpressed, ESCC cell proliferation and invasion were inhibited in vitro and in vivo, which could be elucidated based on changes in gene expression after RNA sequencing, targeted proteomic analysis and bioinformatic assays. However, SOX2 protein did not directly bind to the promoter of miR-142-3p after ChIP sequencing. Together, these findings indicate that a SOX2 regulatory axis governs ESCC proliferation, migration, invasiveness, and apoptosis, thereby providing a potential avenue for future therapeutic intervention. Abbreviations: CCK-8, Cell Counting Kit 8; Chip, Chromatin Immunoprecipitation; EC, Esophageal cancer; EMT, epithelial-to-mesenchymal transition; ESCC, Esophageal squamous cell carcinomas; LLGL2, lethal (2) giant larvae protein homolog 2; LLGL2ov, LLGL2 overexpression; MET, mesenchymal-epithelial transition; miRNAs, MicroRNAs; PRM-MS, Parallel reaction monitoring-Mass spectrometry; SD, Standard deviation; SOX, sex determining region Y (SRY)-like box; SOX2-Kd, SOX2-knockdwon; TUNEL, TdT-mediated dUTP Nick-End Labeling.